PEMILAHAN SAMPAH SEBAGAI SOLUSI PENCEMARAN LINGKUNGAN DALAM NAUNGAN KONSEP AL-SYATHIBI MENGENAI MAQASHID SYARI’AH - Muhammad Labib (PERADA, 2022)
Humans as the caliph of Allah on earth are obliged to guard against mafsadah on the earth they live in. The accumulation of garbage at this time has become one of the mafsadah that needs immediate attention. This is due to population growth, economic growth and changes in people's consumption patterns. One of the problems it causes is the effect of greenhouse gases, which has become a global problem today, in addition to health problems and flooding. In this paper the author will analyze these problems through the concept of maqashid sharia according to Shatiby, where it is concluded that sorting waste is a solution to the problem of environmental pollution caused by landfills. Waste sorting is seen as a form of compassion for the earth and the environment. Without waste sorting, there will be mafsadah, namely the accumulation of waste without being able to be processed instantly even though the final disposal order cannot accommodate more waste. In the end, improper waste management can lead to illness, flooding and even death. This reflects the value of hifdz nafs and hifdz mal. Meanwhile, hifdz din is also found in waste sorting because waste sorting includes ihsan towards the earth, where al-Syathibi stated that ihsan is a form of hifdz din.